La boucle de l’Anthropocène au Sahel : nature et sociétés face aux grands projets environnementaux (Grande Muraille Verte, Sauvegarde du lac Tchad) - Géraud Magrin; Ronan Mugelé (Belgeo)
The global environmental crisis has given major ecological restoration projects a renewed interest from governments. In the Sahel, two examples of these environmental mega projects are designed to combat both desertification and climate change: the construction of the Great Green Wall (GGW) aims to replant degraded soils in semi-arid areas through large-scale planting, while the rescue of Lake Chad consists in developing a water transfer from the Congo Basin to Lake Chad, which is perceived as drying up. This article aims to take a geographical and critical look at these two projects, which are approached here in the light of the concepts of Anthropocene and feedback loop: to what extent can societies turn the telluric force of the Earth system against themselves through large projects that are aimed precisely at mitigating the negative effects of their footprint?